Effectiveness of probiotics in the prevention of carious lesions during treatment with fixed orthodontic appliances - Contreras, Paula; Kay, Jorge; Burgos, Cristian; Contreras, Constanza; Huber, Hinrich (Journal of Oral Research, 2019)
The difficulty experienced by patients with fixed orthodontic appliances in maintaining adequate oral hygiene poses a risk for dental caries. The use of probiotics has been proposed as a means of prevention. The following systematic review aims to determine the effectiveness of probiotics in the prevention of dental caries during treatment with fixed orthodontic appliances. This review was carried out according to the PRISMA guidelines. A comprehensive electronic search was conducted in the Cochrane Library, EMBASE, PubMed and Google Scholar Beta databases. The inclusion criteria included randomized controlled clinical trials involving the use of probiotics, caries and patients under fixed orthodontic treatment. The methodological quality of the articles was evaluated according to risk of bias. Of the five included studies, three reported significant differences compared to the control group. Of the others, one article reported significant decrease in the final count of microorganisms compared to the beginning of treatment. Only one study reported no differences of any kind. It was estimated that the eligible studies were of moderate methodological quality and had an unclear risk of bias, without affecting key domains for the research. It is concluded that the daily consumption of probiotics can be effective in the prevention of carious lesions in patients under fixed orthodontic treatment. However, this should be interpreted with caution and corroborated by clinical trials of better methodological quality.